Rancang Bangun Aplikasi Android Konverter Satuan Berbasis Pengukuran Internasional (Studi Kasus SD Islam Al-Amanah) - Dika Fauzi Nur; Deanna Durbin Hutagalung (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
Abstract− Android is a very useful smarthphone operating system for people to facilitate their activities. One of them is in the fild of learning. Android is able to facilitate in the field of learning supported by available applications. The problem of this research is how to design an Android based unit converter application with Android Studio and how to make students faster in working on conversion problems. This converter aplications aims to convert temperature, distance, time, volume, and weight units automatically and to thefind out the teoritical description of the formula used to get the result of the unit conversion. This converter application will be built using android studio and the model platform software development method. This unite converter application only converts unit of temperature, distance, time, volume, and weight and this application can only run on the Android operating system. This converter applications can run well on Android-based gedgets and can be one of the digital learning media that can help, especially students of SD Islam Al Amanah, Setu Distric in working on Science and Matematics questions, espacially unit conversions and respondents’ responses to this converter applications is feasible to use. This can be seen from the results of the questionnaire calculation as much as as 82.9%. Keywords: Application converter, Android, Android Studio